2018
DOI: 10.1002/jsfa.9084
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol against high ambient temperature‐induced spleen dysplasia in broilers through modulating splenic redox status and apoptosis

Abstract: Resveratrol was effective in ameliorating HT-induced spleen dysplasia in broilers through the activation of the Nrf2 signaling pathway, thereby decreasing apoptosis, suggesting that resveratrol may offer a potential nutritional strategy to protect against some HT-induced detriments. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
4
43
0
Order By: Relevance
“…It has been demonstrated that the stimulation of endogenous antioxidant activity is a major contributor to depressing ROS‐derived oxidative stress . As the first endogenous antioxidant defense, SOD, CAT and GPx are suggested to be important antioxidant enzymes responsible for the removal of ROS . In this study, the activities and expressions of CAT, SOD and GPx were efficiently increased by oral administration of l ‐ methionine, suggesting that the induction of endogenous antioxidant response was clearly dose dependent on l ‐ methionine availability.…”
Section: Discussionmentioning
confidence: 59%
“…It has been demonstrated that the stimulation of endogenous antioxidant activity is a major contributor to depressing ROS‐derived oxidative stress . As the first endogenous antioxidant defense, SOD, CAT and GPx are suggested to be important antioxidant enzymes responsible for the removal of ROS . In this study, the activities and expressions of CAT, SOD and GPx were efficiently increased by oral administration of l ‐ methionine, suggesting that the induction of endogenous antioxidant response was clearly dose dependent on l ‐ methionine availability.…”
Section: Discussionmentioning
confidence: 59%
“…Khazaei et al demonstrated that RSV modulated the expression of elevated RAGE in the liver tissue of diabetic rats; however, the possible mechanisms are unknown . Furthermore, Zhang et al suggest that the inhibition of peroxisome proliferator‐activated‐receptor‐γ (PPARγ) is a possible mechanism for the modulatory effect of RSV on the expression of RAGE . More importantly, evidence exists that RSV disrupts AGE/RAGE signaling by inhibiting MAPK p38, ERK, and NF‐κB pathways …”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, Zhang et al suggest that the inhibition of peroxisome proliferatoractivated-receptor-γ (PPARγ) is a possible mechanism for the modulatory effect of RSV on the expression of RAGE. 62 More importantly, evidence exists that RSV disrupts AGE/RAGE signaling by inhibiting MAPK p38, ERK, and NF-κB pathways. 27 The MGO-degrading capacity of RSV has also emerged as an essential mechanism for detoxifying AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration of the supernatant was assayed by the Bradford method with bovine serum albumin as the standard. The content of serum d ‐lactic acid and jejunum mucosa malondialdehyde (MDA) and protein carbonyl (PC), and the activities of jejunum mucosa total antioxidant capacity (T‐AOC), catalase (CAT), glutathione peroxidase (GSH‐PX) and total superoxide dismutase (T‐SOD) were measured in triplicate using the corresponding commercial assay kits (Nanjing Jiancheng Institute of Bioengineering, Nanjing, China), according to the manufacturer's instructions …”
Section: Methodsmentioning
confidence: 99%